MANAJEMEN PEMBELAJARAN MATA PELAJARAN FIQH MADRASAH TSANAWIYAH NEGERI 1 MANNA KABUPATEN BENGKULU SELATAN - Gustini Gustini (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2017)
Abstract: The results showed that: 1) Planning learning Fiqh in MTsN 1 Manna South Bengkulu consists of: The annual program, the semester program, Syllabus and Learning Implementation Plan (RPP). 2) Implementation of the learning Fiqh in MTsN 1 Manna South Bengkulu consists of initial activities, core activities, and closing activity. The method used is lectures, question and answer, discussion, assignments, modeling, and habituation. The medium used is a whiteboard, markers and pieces of paper. Source of learning comes from the book Fiqh packages class VIII. 3) Evaluation of learning Fiqh in MTsN 1 Manna South Bengkulu include cognitive aspects which consisted of daily tests, midterm replay, replay the end of the semester, and replicates grade. Rate affective aspects done by observing the behavior of students in class directly. Psychomotor assessment done by providing practical assignments.